Effect of Dynamic Balance Training on Agility in Adolescent Volleyball Players - Harsha Vikas Gadre (Journal of Clinical and Diagnostic Research, 2019)
Introduction: Sports training is perching as a new trend and encourages young children to participate in competitive sports. Balance training has been an integral part of conditioning in several sports as it has been a key factor in improving performance of players after sustaining ankle and knee injuries. Aim: To study the effect of active, intensive and dynamic balance training on improving the agility of young volleyball players and comparing effectiveness of the training with gender difference. Materials and Methods: Study design was a one group prepost-test design. Based on inclusion and exclusion criteria, 30 young healthy volleyball players in the age group of 12 to 16 years from a school volleyball team were selected. There were 14 boys and 16 girls. Anthropometric measurements were taken and Body Mass Index (BMI) was calculated for every participant. All the children underwent structured intensive balance training for 4 weeks (6 days/week). Pre and post training t-test of agility assessment was done. Paired t-test applied to see the difference in the performance pre and post training in agility. Unpaired t-test was applied to compare between the pre and post values of the male and female population. Results: Paired t-test, pre and post values of t-test of agility showed significant difference (p<0.05) and unpaired t-test was applied to compare between the pre and post values of male and female population, whereas when compared between boys and girls it did not show clinically significant difference. As per statistical analysis using paired t-test, balance training has a significant impact in improving agility of the young volleyball players. When compared within the groups using unpaired t-test, there was no statistically significant change seen in performance in both boys and girls, but clinically girls showed improvement in agility. Conclusion: Study shows that balance training is effective in improving agility. Clinically females performed better than males but change in performance was not statistically significant. Hence, it can be concluded that balance training is equally effective in improving agility for both genders. From the pre and post training changes in t-test of agility findings it can be concluded that balance training improves agility. Balance training has an equal effect in improving agility for males and females, it is gender indifferent. Scope of further research is there, using multiple outcome measure or with elder age group and larger sample size.